From the East to the West: The Military Orders thematic dossier – A Foreword - Oliveira, Luís Filipe; Leighton, Gregory (Medievalista, 2021)
Following an intense, emotional, and extremely challenging year, it is with great pleasure that we introduce this thematic dossier of Medievalista on the history of the military religious orders. The inspiration for this volume comes from previous talks between Luís Filipe Oliveira and Helen Nicholson, in the summer of 2019, when a series of papers were delivered at the International Medieval Congress in Leeds, England, on the history of the military orders. The four sessions there organized, by Helen Nicholson included several researchers and a variety of topics on the origins of the religious-military orders. From their beginnings in the Eastern Mediterranean and in Europe, to their patrons and growth and to their refoundation and recreation in later times, the scope of the four sessions was wide and comprehensive, presenting new data and information on the continued avenues of ongoing research in the field.